Type 1 insulin-like growth factor receptor inhibition as treatment for urological cancer - Chitnis, M; Dr. Meenali M. Chitnis (2013)
The type 1 insulin-like growth factor receptor (IGF-1R) is a receptor tyrosine kinase that mediates diverse cellular functions including growth, differentiation, migration and apoptosis protection. IGF-1R signalling has been implicated in tumorigenesis in a variety of cancers, and IGF-1R inhibitory drugs are currently undergoing clinical evaluation. Previous work in our laboratory has shown IGF-1R over-expression in urological cancers at both the mRNA and protein level, thus making it a potential therapeutic target. The first aim of this project was to develop a protocol for IGF-1R immunohistochemistry, investigate the expression and cellular distribution of the IGF-1R receptor in clear cell renal cell carcinomas (ccRCC), and assess correlation with clinical parameters. In tissue microarray analysis, IGF-1R was detected in ~90% of 195 ccRCCs, with signal in the plasma membrane, cytoplasm and also in the nucleus. The presence of nuclear IGF-1R in up to 50% of ccRCCs and its association with adverse prognosis was a novel finding, and suggests that nuclear IGF-1R may influence ccRCC biology. Further investigations will clarify its role in the nucleus and its potential as a prognostic biomarker. The second aim was to investigate effects of IGF-1R inhibition on radiosensitivity and DNA repair, following previous work in our laboratory showing that IGF-1R depletion enhances chemo- and radio-sensitivity, delays double strand break (DSB) resolution, and may play a role in the homologous recombination (HR) pathway of DNA DSB repair. However, the repair defect seen in these early experiments was larger than could be entirely explained by a defect in HR. The current project used a small molecule IGF-1R tyrosine kinase inhibitor AZ12253801 (AstraZeneca), which blocked IGF-1 induced IGF-1R activation and inhibited cell survival. AZ12253801 enhanced the radiosensitivity of prostate cancer cells, which appeared to be independent of effects of IGF-1R inhibition on cell cycle distribution and apoptosis induction. IGF-1R inhibition delayed the resolution of γH2AX foci, supporting a potential role for the IGF-1R in DSB repair. This delay in focus resolution was apparent at early time-points (less than 4 hr), and was epistatic with DNA dependent protein kinase (DNAPK) inhibition in prostate cancer cells and DNAPK deficiency in glioblastoma cells. These results suggest a role for the IGF-1R in the non-homologous end-joining (NHEJ) pathway of DNA DSB repair. A cell-based reporter assay in HEK-293 cells confirmed that IGF-1R inhibition suppressed DSB repair by NHEJ, helping to explain the radiosensitization demonstrated upon IGF-1R inhibition. There was lack of support for a transcriptional effect, with no significant change observed in gene expression on microarray analysis. Although the mechanism of this effect remains unclear, the observed inhibition of NHEJ has implications for the use of IGF-1R inhibitors in combination with DNA damaging agents in cancer treatment.